RISK FACTORS FOR DIABETIC FOOT ULCER - Ahmad, Wasim; Khan, Ishtiaq Ali; Ghaffar, Salma; Al-Swailmi, Farhan Khasham; Khan, Ihsanullah (Journal of Ayub Medical College Abbottabad, 2013)
Background: Diabetic foot is one of the common complications of diabetes mellitus. Many risk factors are involved in its causation. This study was conducted to determine risk factors responsible for foot ulcer in diabetic patients. Methods: A total of 196 consecutive patients with diabetic foot were included in the study. Detailed history, clinical findings and investigations were recorded. Lesions were graded according to Wagner’s classification, and appropriate medical and/or surgical treatment was carried out. Patients who did not consent to participate in the study, had established gangrene of the foot, or had any medical co-morbidity especially chronic heart failure and chronic renal failure which could influence these risk factors were excluded from the study. Data were collected on a special proforma for analysis. Results: Out of 196 patients 80.1% were male. One hundred and forty-six (74.48%) patients were in the range of 40-70 years. Right foot was more commonly involved (65.3%), 91.3% patients had diabetes of more than 5 years duration. No treatment had been received by 47.4% patients while 41.3% were on oral anti-diabetics; 11.2% patients were on insulin. All patients had type 2 diabetes mellitus. Neuropathy was present in 51% patients, 62.8% had absent or diminished peripheral pulses, 43.4% had poorly controlled diabetes. According to the Wagner classification 30.6% patients had grade 1, 26.5% had grade 2, and 42.9% had grade 3 diabetic foot. Evidence of infection was seen in 85.7% patients; staphylococcus aureus was isolated in 43.4% patients. Osteomyelitis was present in 42.9% patients. Surgical intervention was performed in 85.7% patients. Direct relation was found between the duration of diabetes, sugar control, peripheral neuropathy, peripheral arterial disease, grade of diabetic foot, evidence of osteomyelitis, intervention and the outcome of the disease. Conclusion: Neuropathy, peripheral arterial disease, duration of diseases and underlying osteomylitis are the major risk factors and need to addressed while educating patients. Keywords: Diabetic foot, Neuropathy, peripheral arterial disease, Angiopathy, Wagner classification